Birchip - Birchip Business and Learning Centre ([Birchip, Vic. : Birchip Business and Learning Centre], 2010)
Website of Birchip, a town in Victoria and the home of the statue "Mallee Bull". Includes community information about Birchip, its history, facilities, and attractions, directories of businesses and community groups and a photo gallery.
Title from home page (viewed on: Mar. 9, 2011)
Text and graphics.
Mode of access: Internet via World Wide Web.
Selected for archiving
Keywords: Birchip (Vic.)